Task-Level Mapping of Electrical and Oil-Handling Risks during Transformer Oil Purification: A Job Safety Analysis at PT PLN Batam - Nanda Putri Utami; Hery Irwan (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2026)
Transformer oil purification combines electrical isolation, auxiliary power, pressurized oil transfer, dielectric testing, and recommissioning, creating interconnected electrical and oil-handling hazards. This study mapped task-level risks and specified stage-specific controls for the purification workflow at PT PLN Batam using Job Safety Analysis. A single-site case study examined ten stages through observation, 30 maintenance interviews, and operational safety-document review. Hazards were classified retrospectively using a 5 × 5 likelihood–severity matrix. Seven stages were rated high risk and three medium risk. Purification-unit connection received the highest score (15) because electrical and oil-transfer interfaces converge at this stage. Proposed controls emphasize verified isolation, lockout/tagout, competent authorization, pressure-rated connections, containment, spill readiness, and independent restoration checks. Under assumed full implementation and verification, the profile is projected to shift to seven medium-risk and three low-risk stages. The study provides a transparent task-level control map while distinguishing projected residual risk from measured outcomes.